Studies on pollen micro-morphology, pollen storage methods, and cross-compatibility among grape (Vitis spp.) genotypes - Rane, Prabhanjan; Thakre, Madhubala; Verma, Mahendra Kumar; Kumar, Chavlesh; Prakash, Jai; Srivastava, Vartika; P. R., Shashank; Murukan, Niranjana; Chawla, Gautam; Mandal, Pranab Kumar; Kumar, Harshit; Jadhav, Amol K.; et al. (Frontiers in Plant Science, 2024)
Ten grape genotypes from three different species viz. Vitis vinifera L., Vitis parviflora Roxb.and Vitis champini Planc. were studied for their pollen structure, and pollen storage with an objective of their utilization in grape rootstock improvement programme. Pollen morphology was examined through the use of a scanning electron microscope (SEM). The viability of the pollen was assessed using 2,3,5-triphenyltetrazolium chloride (TTC). In-vitro pollen germination was investigated using the semi-solid medium with 10% sucrose, 100 mg/L boric acid, and 300 mg/L calcium nitrate. The results revealed variations in pollen micro-morphology in ten genotypes, with distinct pollen dimensions, shapes, and exine ornamentation. But, species-wise, no clear difference was found for these parameters. Pollen of V. parviflora Roxb. and Dogridge were acolporated, which did not germinate. The remaining eight genotypes exhibited tricolporated pollen and showed well in vitro pollen germination. Storage temperature and duration interactions showed that, at room temperature, pollen of most of the grape genotypes can be stored for up to one day only with an acceptable pollen germination rate (>30%). However, storage for up to seven days was successfully achieved at 4°C, except for 'Pearl of Csaba'. The most effective storage conditions were found to be at -20°C and -196°C (in liquid N2), enabling pollen storage for a period of up to 30 days and can be used for pollination to overcome the challenge of asynchronous flowering. Four interspecific combinations were studied for their compatibility among which, V. parviflora Roxb. × V. vinifera L. (Pusa Navrang) and V. parviflora Roxb. × V. champini Planc. (Salt Creek) showed high cross-compatibility, offering their potential use for grape rootstock breeding. However, V. parviflora Roxb. × V. vinifera L. (Male Hybrid) recorded the lowest compatibility index among studied crosses. In the case of self-pollinated flowers from V. parviflora Roxb. and V. parviflora Roxb. × V. champini Planc. (Dogridge), pollen failed to germinate on the stigma due to male sterility caused by acolporated pollen. As a result, the flowers of these genotypes functioned as females, which makes them ideal female parents for grape breeding without the need for the tedious process of emasculation.